2006
DOI: 10.4049/jimmunol.176.9.5191
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Require Multidrug Resistance Protein 1 (ABCC1) Transporter Activity for Differentiation

Abstract: Dendritic cells (DC) express the ATP-binding cassette (ABC) transporters P-glycoprotein (ABCB1) and multidrug resistance protein 1 (MRP1; ABCC1). Functionally, both these transporters have been described to be required for efficient DC and T cell migration. In this study, we report that MRP1 activity is also crucial for differentiation of DC. Inhibition of MRP1, but not P-glycoprotein, transporter activity with specific antagonists during in vitro DC differentiation interfered with early DC development. Impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 40 publications
2
57
0
Order By: Relevance
“…Interestingly, it has been shown that monocytederived dendritic cells require for differentiation multidrug resistance protein 1 (ABCC1) transporter activity, which actively transports LTC 4 out of the cell. 14 Similarly, the activity of both ABCC1 and CysLTs was crucial for CCL19-induced migration of dendritic cells to lymph nodes in vivo in a murine model. 15 In asthmatic patients peripheral blood dendritic cells migrate into the bronchial mucosa during allergic inflammation, 16 and pretreatment with the antileukotriene drug pranlukast significantly attenuates allergen-induced airways responses and alters circulating dendritic cells.…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, it has been shown that monocytederived dendritic cells require for differentiation multidrug resistance protein 1 (ABCC1) transporter activity, which actively transports LTC 4 out of the cell. 14 Similarly, the activity of both ABCC1 and CysLTs was crucial for CCL19-induced migration of dendritic cells to lymph nodes in vivo in a murine model. 15 In asthmatic patients peripheral blood dendritic cells migrate into the bronchial mucosa during allergic inflammation, 16 and pretreatment with the antileukotriene drug pranlukast significantly attenuates allergen-induced airways responses and alters circulating dendritic cells.…”
Section: Introductionmentioning
confidence: 95%
“…37 Similarly, ABCC1 was implicated in the differentiation of a thymoma cell line into CD4 þ CD8 þ cells. 38 Although these studies failed to identify the involved substrates and ABCC1 was not targeted by more specific molecular means, in both these reports it is hypothesized that ABCC1 is important to keep cells in an undifferentiated state, reiterating the possibility that ABC transporters may play a role in the differentiation of mature bone marrow cell types.…”
Section: Abc Transporter Activity As Marker Of Hematopoietic Stem Cellsmentioning
confidence: 99%
“…However, since MRP-1 levels in synovial T cells are rather moderate, a major contribution to a reduced response to MTX or antimalarial drugs remains elusive. Apart from its putative pharmacologic role in MTX extrusion, MRP-1 has an important physiologic function; it exports mediators of inflammation such as leukotriene C 4 , which triggers antigen-presenting dendritic cell migration to lymph nodes via chemoattraction by CCL19 (45,46). Since high levels of CCL19 have been identified in RA synovial tissue (47,48), MRP-1 may be instrumental in the homing of inflammatory cells in RA synovial tissue.…”
mentioning
confidence: 99%